Bibliometric Analysis of Studies on Social Innovation - Kaya Özbağ, Gönül; Esen, Murat; esen, dilek (International Journal of Contemporary Economics and Administrative Sciences, 2019)
The aim of the current study is to examine the scientific publications produced in the field of social innovation (SI) during a period of roughly 40 years through 1975-2018. The analysis based on the bibliometric evaluation of all publications indexed in the Web of Science (WoS) database including "Social Innovation" (SI) phrase in the title, abstract or key words. The research is carried out through parameters including the number of publications in line with the years, authors, journals and country, publication types, citation analyses, collaborations and also concept-topic tendencies. Results indicated that the vast majority of SI studies are published as an “article”. Respectively, UK, USA and Italy are the top three leading countries that contribute to the SI literature. Design Journal” is a prominent domain of SI research and the field is multidisciplinary. Findings also demonstrated that Mumford Michael D. is the most productive scholar in the field of SI whereas Swyngedouw E. produced the most cited article in the WOS. Finally, a significant increase in the number of publications published in SI field is remarkable since 2015 which leads the conclusion that the topic has gained momentum in recent years among the academicians.